Blood-Enriching Effects and Immune-Regulation Mechanism of Steam-Processed Polygonatum Sibiricum Polysaccharide in Blood Deficiency Syndrome Mice - Wang, Juan; Wang, Furong; Yuan, Lixia; Ruan, Hongsheng; Zhu, Zhibiao; Fan, Xiaoling; Zhu, Lingyan; Peng, Xin (Frontiers in Immunology, 2022)
Polygonatum sibiricum Red. has been used as a medicinal herb and nutritional food in traditional Chinese medicine for a long time. It must be processed prior to clinical use for safe and effective applications. However, the present studies mainly focused on crude Polygonatum sibiricum (PS). This study aimed to investigate the chemical properties, blood-enriching effects and mechanism of polysaccharide from the steam-processed Polygonatum sibiricum (SPS), which is a common form of PS in clinical applications. Instrumentation analyses and chemistry analyses revealed the structure of SPS polysaccharide (SPSP). A mice model of blood deficiency syndrome (BDS) was induced by acetylphenylhydrazine (APH) and cyclophosphamide (CTX). Blood routine test, spleen histopathological changes, serum cytokines, etc were measured. The spleen transcriptome changes of BDS mice were detected by RNA sequencing (RNA-seq). The results showed that SPSP consists predominantly of Gal and GalA together with fewer amounts of Man, Glc, Ara, Rha and GlcN. It could significantly increase peripheral blood cells, restore the splenic trabecular structure, and reverse hematopoietic cytokines to normal levels. RNA-seq analysis showed that 122 differentially expressed genes (DEGs) were obtained after SPSP treatment. GO and KEGG analysis revealed that SPSP-regulated DEGs were mainly involved in hematopoiesis, immune regulation signaling pathways. The reliability of transcriptome profiling was validated by quantitative real-time PCR and Western blot, and the results indicated that the potential molecular mechanisms of the blood-enriching effects of SPSP might be associated with the regulating of JAK1-STAT1 pathway, and elevated the hematopoietic cytokines (EPO, G-CSF, TNF-α and IL-6). This work provides important information on the potential mechanisms of SPSP against BDS.